DETERMINACIÓN DE COSTOS UNITARIOS DE PRODUCCIÓN EN LA EMPRESA LÁCTEOS SARAGURO, MEDIANTE LA IMPLEMENTACIÓN DE UN SISTEMA DE CONTABILIDAD DE COSTOS - Macas Andrade, Hilda Narcisa (2019)
The thesis entitled: "DETERMINATION OF UNITARY COSTS OF PRODUCTION IN THE SARAGURO DAIRY COMPANY, BY IMPLEMENTATION OF A COSTS ACCOUNTING SYSTEM" was executed with the purpose of contributing to the development of the Cost Accounting System by Production Orders, especially to give solution to the problems found, the same one that require efficient procedures that allow maximizing the investment of the company and the achievement of the short and long term objectives of the same one. The methodology used is non-experimental and descriptive, as it is based on the collection of information through an interview applied directly to the owner of the company, which showed the lack of knowledge on the proper management and control of cost elements at the time of obtaining a finished product. In order to comply with the proposed objectives, a matrix was elaborated where the criteria were established to determine the adequate cost system for the company according to the nature of the same, continuing with the execution of the respective auxiliaries such as production orders, purchase request, purchase orders, report of receipt of materials, orders of requisition of materials, cost sheets and kardex, this allowed the adequate control of the three elements of cost such as raw material, labor and indirect manufacturing costs, which served to obtain the total and unit cost of each production order generated during the process of transformation of raw material into finished product. Likewise, the accounting process was developed by the system of costs for production orders based on the source documentation that justifies the 5 transactions recorded, as well as the chronological and sequential day-to-day journal entries in the journal to then group the various accounts and proceed to the preparation and presentation of financial statements such as: statement of costs of products sold, shows a real cost of $24.271.00 grouping the three elements of the cost, Statement of Results that expresses a net profit of $10.403,93 value considered after deducting all the expenses of the company, Statement of Financial Situation details a total of assets of $94.900,42 liabilities with $16.164,51 and an equity of $78.735,91 and the Statement of Cash Flow informs on the variations and movements of cash and its equivalents with an increase of $4.816,77 these figures demonstrate the financial and economic situation of the business. Finally, it is concluded that the application of the system of production order costs in the Saraguro, dairy company, served as a tool to efficiently allocate the manufacturing costs that intervene directly and indirectly to each product offered by the entity.